Gastroschisis: factors influencing 3-year survival and digestive outcome - Lília Valente; Susana Pissarra; Tiago Henriques-Coelho; Filipa Flor-; Hercília Guimarães (Hygeia Press di Corridori Marinella, 2015)
Background: Gastroschisis patients' morbidity is still high, underlining the importance of identifying factors associated with adverse outcomes. Objective: To determine factors influencing gastroschisis patients' morbimortality during the first 3 years of life in "Centro Hospitalar São João" (CHSJ). Methodology: Records of infants born with gastroschisis between January 2002 and December 2011 admitted to CHSJ were reviewed. The relation between demographic and clinical data and morbimortality during the first 3 years of life, specifically anthropometric evolution and digestive outcome, was evaluated. The factors that were compared were simple versus complex gastroschisis and primary versus secondary closure. Results: Forty records were analysed. The survival rate was 92.3%. Patients with complex gastroschisis had worse outcomes: hospital stay (median 59 versus 23.5 days), total parenteral nutrition (50 versus 19 days), total oral intake reached (47 versus 22.5 days), morphine analgesia (9 versus 3 days), intestinal occlusion (60% versus 11.8%), perforation (60% versus 0%) and ischaemia (40% versus 0%), sepsis (100% versus 32.4%), short bowel syndrome (40% versus 3.1%), laxative need during 1-year follow-up (40% versus 0%), weight percentile < 5 at 6 months (75% versus 13.6%) and gastrointestinal symptoms after the first year of life (OR: 42; 95% CI: 2.01-877.5). Secondary closure patients had worse outcomes: start of oral intake (25 versus 11.5 days), total oral intake reached (48 versus 23 days), necrotizing enterocolitis (40% versus 2.9%) and mortality (40% versus 2.9%). Conclusion: Complex gastroschisis and secondary closure were both associated with higher morbidity. Secondary closure was also associated with higher mortality. Complex gastroschisis revealed to be a predictive factor for higher incidence of gastrointestinal symptoms after the first year of life. Therefore, follow-up at least until 3 years of life of patients with complex gastroschisis is recommended. Further research is needed to determine management strategies that improve prognosis.